Health service needs of older persons: emerging findings from Tarakan City, East Kalimantan - Kusumaratna, Rina K.; Mahmood, Mohammad Afzal; Soerjoasmoro, Maskito Asmadi; Khairul, Khairul (Universa Medicina, 2011)
As older persons are steadily increasing in number and there are no specialized comprehensive healthcare services for older persons in Indonesia, including East Kalimantan, the aim of the present study was to determine the extent of the problems facing healthcare staff and officials in Tarakan City, East Kalimantan, in providing comprehensive healthcare services attuned to the needs of older persons.This study was a qualitative interview-based survey with focus group discussions, involving heads and healthcare officials of seven puskesmas in Tarakan City, East Kalimantan district, with the addition of a number of district health planning officials. The results revealed a difference between daily hospital referral rate of older persons by puskesmas staff and actual daily hospital admission rate for the referrals. None of the consulted healthcare staff had any speciality education in geriatrics or older persons health. The older persons most frequently presented to the hospital with hypertension, diabetes, and myocardial insufficiency. On the other hand, at the health centers the presenting conditions were hypertension, gastroenteritis, rheumatism, sleep disorders, and upper respiratory tract infections. Improved access to healthcare for older persons should be achieved by improving knowledge and skills of human resources, including communication skills, and of supporting healthcare service infrastructure at puskesmas, specifically oriented towards the needs of and designed for use by older persons, such as ramps for wheelchairs, and handrails in corridors. Local governments should strengthen the appropriate service delivery to older persons, and provide support for the maintenance, sustainability and strengthening of community-based care for older persons.